Corporate Social Responsibility: Analysis Of Green Financial Behavior, Political Connections, Corporate Financial Performance And Sustainability Development - Nabilah Qurrotul ’Aini; Ruri Istia Damayanti; Hwihanus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Research or researching five international journals on corporate social responsibilities, political connections, corporate financial performance and sustainable development aimed at analyzing links between corporate social responsibility (CSR) and green financial behaviors, political connections, corporate financial performance, and sustainability. Research methods are employed with descriptive qualitative methods of searching through top five international academic databases such as science direct, emerald, and taylorandfrancis, with emphasis on publications that include aspects of corporate social responsibility. The results from a study of the five journals say that companies that have good CSR policies tend to be more active in implementing green finance practices, such as investments in renewable energy and resource efficiency. In addition, companies with strong political connections have easier access to resources and business opportunities that can improve their financial performance. Furthermore, effective CSR applications prove to have a positive impact on sustainability development, with companies contributing more significantly to environmental and social initiatives. It is hoped that the findings will provide insights for stakeholders in CSR relevant strategic decision making and company sustainability